Distribution of phosphorus forms in surface soils of typical peatlands in northern Great Khingan Mountains and its potential to reconstruct paleo-vegetations. (15th January 2022) - Li, Yunhui; Gao, Chuanyu; Liu, Hanxiang; Han, Dongxue; Cong, Jinxin; Li, Xiao; Wang, Guoping
Abstract: Phosphorus was one of the nutrient limitations to vegetations in wetland ecosystem. In peatland, organic phosphorus is accumulated as vegetation residues in anaerobic conditions, affecting the contents of phosphorus pools for long time. It is unclear that different vegetations affect the contents of phosphorus and whether successions of vegetations could reflected by sedimentation of phosphorus forms. Phosphorus forms from six surface soils plots and four dominant vegetations in the north of the Great Khingan mountains were detected to investigate the differences of phosphorus forms of soil between different vegetations. Phosphorus forms and macrofossil were also detected in a 77-cm peat core (1-cm intervals) in TQ. A fingerprinting historical vegetations were reconstructed by phosphors forms to reflect successions of vegetations during 2200 cal yr BP in TQ area. The results showed that the main phosphorus forms in peatland were NaOH-Po and conc. HCl-Po . The percentages of inorganic phosphorus forms of trees were generally higher than other vegetations. Moss was more conducive for accumulation of organic phosphorus. NaHCO3 -Pi, NaOH-Pi, conc. HCl-Po and Pi were selected into linear discrimination analysis. The vegetations reconstructed by phosphorus forms were strongly correlated with the pollen records of moss, herbs and shrubs, as well as with macrofossils in herbs. The fingerprinting of vegetations by phosphorus has potential geochemical reference to reflect the successions of vegetation in peatland. Highlights: The inorganic phosphorus forms of trees were higher in peatlands. The organic phosphorus forms of moss were higher than herbs, shrub and trees. Four phosphorus forms were used to reconstruct succession of vegetations. Phosphorus forms reconstructed changes of vegetations of moss, herbs and shrubs.